A high and low temperature resistant nylon material and preparation method thereof
By introducing toughened particles and high-temperature resistance additives with organic-inorganic interpenetrating network structure into nylon 66, the problem of nylon 66 being easily brittle at low temperatures and insufficient high-temperature resistance at high temperatures is solved, and the excellent performance of the material in high and low temperature environments is achieved.
Patent Information
- Application Number
- CN202410366375.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-28
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-03-28
AI Technical Summary
Nylon 66 is prone to become brittle at low temperatures, has poor low-temperature impact performance, and is insufficient in high-temperature environments, making it difficult to use in long-term high-temperature, high-humidity and oxygen environments.
Toughening particles and high-temperature resistance additives with organic-inorganic interpenetrating network structure are adopted. Particles of organic-inorganic interpenetrating network structure formed by adding elastomers, inorganic porous particles, and epoxy resin to nylon 66, and high-temperature resistance additives of titanate, long-carbon chain calcium carboxylate salt, silicone, calcium sulfate whiskers and other materials are used to improve the high-temperature resistance of the material.
It realizes the toughening of nylon materials at low temperatures and heat resistance at high temperatures, and can be used in a high temperature environment of 210℃ for a long time without deformation, which significantly improves the application range and performance of the material.
Smart Images

Figure BDA0004764352670000071 
Figure BDA0004764352670000072 
Figure BDA0004764352670000082
Abstract
Description
Technical Field
[0001] The invention belongs to the field of high-performance nylon engineering plastics, and particularly relates to a high and low temperature resistant nylon material and a preparation method thereof. Background Art
[0002] As an engineering plastic with heat resistance, chemical resistance, high strength and high wear resistance, nylon has been widely used in automotive parts such as engine parts, door handles, rearview mirror frames, bumpers, etc. In particular, it is widely used in some special functional parts such as electrical and electronic insulation parts, precision electronic instrument parts, switches, gears, lubricated bearings, etc. Nylon 66 (scientific name: polyhexamethylene adipamide, industrial abbreviation: PA66) has the characteristics of high fatigue strength, high rigidity, good heat resistance and good wear resistance. It has been widely used in mechanical wear-resistant parts, precision gears, oil-free lubricated bearings, engine fan blades, engine intake pipes, automotive air conditioning evaporators and other fields. However, due to the poor low-temperature impact strength and low heat deformation temperature of nylon 66, the application of PA66 in long-term high and low temperature environments is limited. Therefore, improving the high and low temperature resistance of nylon is particularly critical to expanding the application of nylon.
[0003] Nylon 66 quickly becomes brittle at low temperatures, and its low-temperature impact performance is too low, so it usually needs toughening treatment. Currently, the commonly used nylon toughening agents are mainly thermoplastic elastomers, which usually introduce soft elastomer molecules into the nylon structure. When subjected to external impact, the soft polyolefin elastomer absorbs energy. At low temperatures, polyolefin elastomers have a lower glass transition temperature, which can help achieve toughening of nylon in low-temperature environments and prevent brittleness.
[0004] China Invention Patent Publication No. CN114316583A discloses a high-toughness and high-temperature resistant nylon composite material and its preparation method, which improves the toughness of nylon by using a star-shaped nylon with a specific molecular weight and a specific molecular structure containing an ether bond as the core as a toughening modifier. China Invention Patent Publication No. CN117165077A discloses a nylon 66 material and its preparation method, which improves the rigidity, hardness, creep behavior and thermal stability of the material by using a compound reinforcing agent (short glass fiber, nano-scale carbon black powder, ultrafine calcium carbonate powder).
[0005] However, with the introduction of polyolefin elastomers, the heat resistance of nylon in high temperature environments has deteriorated. The thermal deformation of nylon materials is mainly manifested in the product undergoing a large deformation and losing its original shape and size, resulting in problems such as inaccurate part size, deformation, and cracking. The addition of thermoplastic elastomers will reduce the rigidity of nylon and its high temperature resistance, making it difficult to achieve both high and low temperature resistance at the same time.
[0006] The use of glass fiber reinforced nylon 66 can improve the physical and mechanical properties of nylon 66 while also greatly improving its high temperature resistance. Generally, the high temperature resistance of glass fiber reinforced nylon 66 can be increased to 150-200°C. However, due to the structure of nylon 66 itself, it has poor water resistance and is prone to react with oxygen in high temperature environments, accelerating decomposition. Therefore, even modified and reinforced nylon 66 materials are difficult to use for a long time in an environment of 150-200°C in a high temperature, high humidity, and oxygen environment. Summary of the invention
[0007] As the application scenarios of nylon 66 change, the requirements for it are getting higher and higher. In view of the current problems of poor low-temperature toughness and easy deformation at high temperatures when nylon 66 is used in engineering parts, the present invention proposes a nylon material that can take into account both high and low temperature resistance. Its outstanding technical feature is the use of toughening particles with an organic-inorganic interpenetrating network structure, which can withstand high temperatures while solving the problem of nylon's embrittlement at low temperatures; and the use of high-temperature resistant additives to make nylon less likely to deform at high temperatures and adapt to long-term work in high-temperature environments.
[0008] To achieve the above technical objectives, the present invention is implemented through the following specific technical solutions.
[0009] The first aspect of the present invention is to provide a high and low temperature resistant nylon material. Calculated by weight, the composition of the high and low temperature resistant nylon material includes: 45 to 60 parts of nylon 66, 35 to 45 parts of reinforcing fiber, 5 to 10 parts of low temperature toughening aid, 3 to 5 parts of high temperature resistant aid, 0.5 to 1 part of inorganic lubricant, 0.2 to 0.5 parts of compatibilizer, 0.2 to 0.5 parts of antioxidant, and 0.2 to 0.5 parts of copper salt heat stabilizer; wherein the low temperature toughening aid is an organic-inorganic interpenetrating network structure particle of an elastomer, an inorganic porous particle, and an epoxy resin blended and extruded in a mass ratio of 3 to 5:5 to 6:1; the high temperature resistant aid is a composite of titanate, a long carbon chain carboxylic acid calcium salt, silicone, and a calcium sulfate whisker in a mass ratio of 1:2:2:4.
[0010] Preferably, the reinforcing fibers are alkali-free continuous glass fibers with a fiber diameter of 7 to 13 μm.
[0011] Preferably, the inorganic lubricant is selected from one or more of tungsten disulfide, molybdenum disulfide, graphite, barium sulfate, and glass microspheres. The inorganic lubricant has a layered or spherical structure, is easy to slide, can effectively avoid thermal degradation during nylon processing, reduce the use of low molecular weight lubricants, and enhance the high temperature resistance of nylon.
[0012] Preferably, the compatibilizer is a silane coupling agent.
[0013] Preferably, the antioxidant is selected from one or more of hindered phenol antioxidants, amine antioxidants, phosphorus antioxidants, thioether antioxidants, and metal passivators. Antioxidant 1098 is particularly preferred.
[0014] Preferably, the copper salt heat stabilizer is selected from copper phthalocyanine and copper acetate. The copper salt heat stabilizer can effectively inhibit the decomposition of nylon at high temperature, improve its heat resistance, and effectively avoid yellowing and brittleness and mechanical property degradation caused by thermal oxidation degradation during processing in a fiber-reinforced system, thereby preventing nylon from becoming brittle and losing mechanical properties at high temperature.
[0015] The second aspect of the present invention is to provide a method for preparing a high and low temperature resistant nylon material, and the specific preparation method is as follows:
[0016] S1: The elastomer, inorganic porous particles and epoxy resin are uniformly mixed in a mass ratio of 3-5:5-6:1, and the mixture is extruded through a twin-screw extruder to form particles with an organic-inorganic interpenetrating network structure as a low-temperature toughening agent;
[0017] S2: Titanate, long carbon chain carboxylic acid calcium salt, silicone, and calcium sulfate whisker are dispersed at a mass ratio of 1:2:2:4 to obtain a high temperature resistant additive;
[0018] S3: 45-60 parts by weight of nylon 66, 5-10 parts of the low-temperature toughening agent prepared in step S1, 3-5 parts of the high-temperature resistant agent prepared in step S2, 0.5-1 part of an inorganic lubricant, 0.2-0.5 parts of a compatibilizer, 0.2-0.5 parts of an antioxidant, and 0.2-0.5 parts of a copper salt heat stabilizer are uniformly dispersed in a homogenizing pot, and the uniformly dispersed mixture is added to a co-rotating twin-screw extruder for melt extrusion and granulation, and continuous glass fiber is added to the 5th to 6th shearing zone of the co-rotating twin-screw extruder at the same time, and the screw speed and the number of glass fibers added are adjusted to control the fiber weight to 35-45 parts; a high and low temperature resistant nylon material is obtained through screw shearing dispersion, melt extrusion drawing, chain air cooling, pelletizing, screening, drying, and packaging.
[0019] Preferably, the elastomer in step S1 is selected from one or more of styrene-maleic anhydride copolymer, maleic anhydride grafted SEBS, maleic anhydride grafted ethylene-octene copolymer (POE-g-MAH), and maleic anhydride grafted ethylene propylene diene monomer rubber (EPDM-g-MAH).
[0020] Preferably, the inorganic porous particles in step S1 are inorganic particles with a particle size of less than 2 μm and a microporous structure, and fumed silica is particularly preferred.
[0021] Preferably, vacuum exhaust ports are provided in zones 3 and 8 of the co-rotating twin-screw extruder in step S3. When the nylon in zone 3 is completely melted, trace moisture contained in the nylon is promptly removed through the vacuum exhaust port to avoid nylon degradation during the post-break shear dispersion. When the nylon blending modification in zone 8 is in the shear dispersion compression stage, the generated volatiles are promptly removed through the vacuum exhaust port.
[0022] Preferably, the co-rotating twin-screw extruder in step S3 uses a screw with a length-to-diameter ratio of 40:1; the temperature control of each temperature control zone of the extruder is: zone 1 240-260°C; zone 2 270-275°C; zone 3 280-285°C; zone 4 270-275°C; zone 5 260-265°C; zone 6 240-250°C; zone 7 220-230°C; zone 8 200-210°C; zone 9 200-210°C; zone 10 200-210°C.
[0023] The present invention preforms an elastomer, inorganic porous particles, and epoxy resin into a low-temperature toughening agent, and forms interpenetrating network particles under the action of epoxy resin bonding and inorganic porous particles. On the one hand, it has the function of preventing nylon from becoming brittle at low temperatures and improving low-temperature toughness. On the other hand, the toughening particles composed of the elastomer and the inorganic porous particles are evenly dispersed in the nylon matrix continuous phase during hot melting, and a micro-crosslinking reaction occurs at the interface of the epoxy resin and the nylon. The evenly distributed micro-crosslinking network structure effectively transmits stress to restrain the movement of the molecular chain, thereby achieving a toughening effect. In particular, the low-temperature toughening agent preformed with the elastomer and the inorganic porous particles yields slowly under high-temperature conditions of nylon, and its heat resistance is improved.
[0024] Furthermore, the high temperature resistant additive of the present invention is quickly separated into fine particles during hot melt extrusion processing, which promotes the homogenization and reduction of the spherulite size of nylon 66 crystallization. With the assistance of calcium sulfate whiskers, the high temperature resistance is significantly improved, which not only increases the heat deformation temperature, but also allows long-term use at high temperatures without deformation.
[0025] A high and low temperature resistant nylon material and a preparation method thereof have significant advantages over the prior art in that:
[0026] (1) In the present invention, organic-inorganic interpenetrating network particles are added to the glass fiber reinforced nylon 66 system, and the micro-crosslinked network structure effectively restrains the movement of molecular chains, thereby achieving a toughening effect. At the same time, the yielding is slowed down at high temperatures, thereby improving the heat resistance.
[0027] (2) The high temperature resistant additive composed of titanate, long carbon chain carboxylic acid calcium salt, silicone and calcium sulfate whisker is dispersed into fine particles in nylon, which promotes the reduction of the size of nylon 66 spherulites. With the assistance of calcium sulfate whisker, it can be used for a long time at high temperature without deformation.
[0028] (3) The synergistic use of copper heat stabilizers and inorganic lubricants can effectively avoid shear degradation of nylon when it is reinforced with glass fibers, and the glass fibers and nylon maintain good reinforcement, stiffness enhancement, and high-temperature dimensional stability.
[0029] (4) The preparation technology of the present invention is easy to control and suitable for large-scale production. The nylon material is suitable for use in high and low temperature environments, especially for long-term use in a high temperature environment of 210°C. DETAILED DESCRIPTION
[0030] The technical advantages and practical value of the present invention are significantly improved over the existing technology, and the technical products are suitable for large-scale production. In order to make the purpose and technical advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described in conjunction with the embodiments below. Based on the embodiments of the present invention, the solutions proposed by ordinary technicians in this field based on the ideas of the present invention without making creative work all belong to the scope of protection of the present invention.
[0031] In the examples, any specific steps or process conditions not specified were processed according to conventional processes in the art; any raw materials not specifically specified were conventional raw materials that can be purchased commercially.
[0032] Example 1
[0033] S1: Maleic anhydride grafted ethylene-octene copolymer, fumed silica with a particle size of less than 2 μm, and bisphenol A epoxy resin SM601 are uniformly mixed in a mass ratio of 5:6:1, and extruded through a twin-screw extruder at 180° C. to form particles with an organic-inorganic interpenetrating network structure as a low-temperature toughening additive;
[0034] S2: Titanate, long carbon chain carboxylic acid calcium salt, silicone, and calcium sulfate whisker are dispersed at a mass ratio of 1:2:2:4 to obtain a high temperature resistant additive;
[0035] S3: Disperse 55 parts of nylon 66, 10 parts of the low-temperature toughening agent prepared in step S1, 5 parts of the high-temperature resistant agent prepared in step S2, 1 part of glass microspheres, 0.5 parts of silane coupling agent, 0.3 parts of antioxidant 1098, and 0.2 parts of copper acetate in a homogenizing pot according to weight, add the dispersed mixture into a co-rotating twin-screw extruder for melt extrusion and granulation, the aspect ratio of the screw is 40:1, and the temperature of each temperature control zone is controlled as follows: Zone 1 240°C; Zone 2 270°C; Zone 3 280°C; Zone 4 270°C; Zone 5 260℃; 250℃ in zone 6; 230℃ in zone 7; 210℃ in zone 8; 200℃ in zone 9; 200℃ in zone 10; add alkali-free continuous glass fiber with a fiber diameter of 7-13μm in the 5th shearing zone, adjust the screw speed and the number of glass fibers added to control the fiber weight to 35 parts; set vacuum exhaust ports in zones 3 and 8, and remove the generated volatile water in time through the vacuum exhaust ports; through screw shearing dispersion, melt extrusion drawing, chain air cooling, pelletizing, screening, drying and packaging, a high and low temperature resistant nylon material is obtained.
[0036] Example 2
[0037] S1: Maleic anhydride grafted EPDM rubber, fumed silica with a particle size of less than 2 μm, and bisphenol A epoxy resin SM601 are uniformly mixed in a mass ratio of 5:6:1, and extruded through a twin-screw extruder at 200° C. to form particles with an organic-inorganic interpenetrating network structure as a low-temperature toughening additive;
[0038] S2: Titanate, long carbon chain carboxylic acid calcium salt, silicone, and calcium sulfate whisker are dispersed at a mass ratio of 1:2:2:4 to obtain a high temperature resistant additive;
[0039] S3: According to weight, 55 parts of nylon 66, 10 parts of the low-temperature toughening agent prepared in step S1, 4 parts of the high-temperature resistant agent prepared in step S2, 1 part of molybdenum disulfide, 0.5 parts of silane coupling agent, 0.2 parts of antioxidant 1098, 0.1 parts of antioxidant 168, and 0.3 parts of copper acetate are dispersed evenly in a homogenizing pot, and the evenly dispersed mixture is added to a co-rotating twin-screw extruder for melt extrusion and granulation. The aspect ratio of the screw is 40:1, and the temperature of each temperature control zone is controlled as follows: 240°C for zone 1; 270°C for zone 2; 280°C for zone 3; and 2 70℃; 260℃ in zone 5; 250℃ in zone 6; 230℃ in zone 7; 210℃ in zone 8; 200℃ in zone 9; 200℃ in zone 10; add alkali-free continuous glass fiber with a fiber diameter of 7-13μm in the 5th shearing zone, adjust the screw speed and the number of glass fibers added to control the fiber weight to 40 parts; set vacuum exhaust ports in zones 3 and 8, and remove the generated volatile water in time through the vacuum exhaust ports; through screw shearing dispersion, melt extrusion drawing, chain air cooling, pelletizing, screening, drying and packaging, a high and low temperature resistant nylon material is obtained.
[0040] Example 3
[0041] S1: Maleic anhydride grafted EPDM rubber, fumed silica with a particle size of less than 2 μm, and bisphenol A epoxy resin SM601 are uniformly mixed in a mass ratio of 3:6:1, and extruded through a twin-screw extruder at 200° C. to form particles with an organic-inorganic interpenetrating network structure as a low-temperature toughening additive;
[0042] S2: Titanate, long carbon chain carboxylic acid calcium salt, silicone, and calcium sulfate whisker are dispersed at a mass ratio of 1:2:2:4 to obtain a high temperature resistant additive;
[0043] S3: According to weight, 55 parts of nylon 66, 10 parts of the low-temperature toughening agent prepared in step S1, 4 parts of the high-temperature resistant agent prepared in step S2, 1 part of barium sulfate, 0.5 parts of silane coupling agent, 0.2 parts of antioxidant 1098, 0.1 parts of antioxidant 168, and 0.3 parts of copper acetate are dispersed evenly in a homogenizing pot, and the evenly dispersed mixture is added to a co-rotating twin-screw extruder for melt extrusion and granulation. The aspect ratio of the screw is 40:1, and the temperature of each temperature control zone is controlled as follows: 240°C for zone 1; 270°C for zone 2; 280°C for zone 3; and 270°C for zone 4. 0℃; 260℃ in zone 5; 250℃ in zone 6; 230℃ in zone 7; 210℃ in zone 8; 200℃ in zone 9; 200℃ in zone 10; add alkali-free continuous glass fiber with a fiber diameter of 7-13μm in the 5th shearing zone, adjust the screw speed and the number of glass fibers added to control the fiber weight to 40 parts; set vacuum exhaust ports in zones 3 and 8, and remove the generated volatile water in time through the vacuum exhaust ports; through screw shearing dispersion, melt extrusion drawing, chain air cooling, pelletizing, screening, drying and packaging, a high and low temperature resistant nylon material is obtained.
[0044] Example 4
[0045] S1: Maleic anhydride grafted SEBS, fumed silica with a particle size of less than 2 μm, and bisphenol A epoxy resin SM601 are uniformly mixed in a mass ratio of 5:6:1, and extruded through a twin-screw extruder at 200°C to form particles with an organic-inorganic interpenetrating network structure as a low-temperature toughening additive;
[0046] S2: Titanate, long carbon chain carboxylic acid calcium salt, silicone, and calcium sulfate whisker are dispersed at a mass ratio of 1:2:2:4 to obtain a high temperature resistant additive;
[0047] S3: According to weight, 55 parts of nylon 66, 10 parts of the low-temperature toughening agent prepared in step S1, 5 parts of the high-temperature resistant agent prepared in step S2, 1 part of graphite, 0.5 parts of silane coupling agent, 0.2 parts of antioxidant 1098, 0.1 parts of antioxidant 168, and 0.3 parts of copper acetate are dispersed evenly in a homogenizing pot, and the evenly dispersed mixture is added to a co-rotating twin-screw extruder for melt extrusion and granulation. The aspect ratio of the screw is 40:1, and the temperature of each temperature control zone is controlled as follows: 240°C for zone 1; 270°C for zone 2; 280°C for zone 3; and 270°C for zone 4. 0℃; 260℃ in zone 5; 250℃ in zone 6; 230℃ in zone 7; 210℃ in zone 8; 200℃ in zone 9; 200℃ in zone 10; add alkali-free continuous glass fiber with a fiber diameter of 7-13μm in the 5th shearing zone, adjust the screw speed and the number of glass fibers added to control the fiber weight to 38 parts; set vacuum exhaust ports in zones 3 and 8, and remove the generated volatile water in time through the vacuum exhaust ports; through screw shearing dispersion, melt extrusion drawing, chain air cooling, pelletizing, screening, drying and packaging, a high and low temperature resistant nylon material is obtained.
[0048] Comparative Example 1
[0049] S1: Maleic anhydride grafted ethylene-octene copolymer, calcium carbonate with a particle size of less than 2 μm, and bisphenol A epoxy resin SM601 are uniformly mixed in a mass ratio of 5:6:1, and extruded through a twin-screw extruder at 180° C. to form particles with an organic-inorganic interpenetrating network structure as a low-temperature toughening additive;
[0050] S2: Titanate, long carbon chain carboxylic acid calcium salt, silicone, and calcium sulfate whisker are dispersed at a mass ratio of 1:2:2:4 to obtain a high temperature resistant additive;
[0051] S3: Disperse 55 parts of nylon 66, 10 parts of the low-temperature toughening agent prepared in step S1, 5 parts of the high-temperature resistant agent prepared in step S2, 1 part of glass microspheres, 0.5 parts of silane coupling agent, 0.3 parts of antioxidant 1098, and 0.2 parts of copper acetate in a homogenizing pot according to weight, add the dispersed mixture into a co-rotating twin-screw extruder for melt extrusion and granulation, the aspect ratio of the screw is 40:1, and the temperature of each temperature control zone is controlled as follows: Zone 1 240°C; Zone 2 270°C; Zone 3 280°C; Zone 4 270°C; Zone 5 260℃; 250℃ in zone 6; 230℃ in zone 7; 210℃ in zone 8; 200℃ in zone 9; 200℃ in zone 10; add alkali-free continuous glass fiber with a fiber diameter of 7-13μm in the 5th shearing zone, adjust the screw speed and the number of glass fibers added to control the fiber weight to 35 parts; set vacuum exhaust ports in zones 3 and 8, and remove the generated volatile water in time through the vacuum exhaust ports; through screw shearing dispersion, melt extrusion drawing, chain air cooling, pelletizing, screening, drying and packaging, a high and low temperature resistant nylon material is obtained.
[0052] Comparative Example 2
[0053] S1: Maleic anhydride grafted EPDM rubber, fumed silica with a particle size of less than 2 μm, and bisphenol A epoxy resin SM601 are uniformly mixed in a mass ratio of 5:6:1, and extruded through a twin-screw extruder at 200° C. to form particles with an organic-inorganic interpenetrating network structure as a low-temperature toughening additive;
[0054] S2: Pre-prepare a high temperature resistant additive by dispersing titanate and calcium sulfate whiskers at a mass ratio of 1:4 at high speed;
[0055] S3: According to weight, 55 parts of nylon 66, 10 parts of the low-temperature toughening agent prepared in step S1, 4 parts of the high-temperature resistant agent prepared in step S2, 1 part of molybdenum disulfide, 0.5 parts of silane coupling agent, 0.2 parts of antioxidant 1098, 0.1 parts of antioxidant 168, and 0.3 parts of copper acetate are dispersed evenly in a homogenizing pot, and the evenly dispersed mixture is added to a co-rotating twin-screw extruder for melt extrusion and granulation. The aspect ratio of the screw is 40:1, and the temperature of each temperature control zone is controlled as follows: 240°C for zone 1; 270°C for zone 2; 280°C for zone 3; and 2 70℃; 260℃ in zone 5; 250℃ in zone 6; 230℃ in zone 7; 210℃ in zone 8; 200℃ in zone 9; 200℃ in zone 10; add alkali-free continuous glass fiber with a fiber diameter of 7-13μm in the 5th shearing zone, adjust the screw speed and the number of glass fibers added to control the fiber weight to 40 parts; set vacuum exhaust ports in zones 3 and 8, and remove the generated volatile water in time through the vacuum exhaust ports; through screw shearing dispersion, melt extrusion drawing, chain air cooling, pelletizing, screening, drying and packaging, a high and low temperature resistant nylon material is obtained.
[0056] Comparative Example 3
[0057] The same process as in Example 1 was performed, except that no low-temperature toughening agent was added.
[0058] Comparative Example 4
[0059] The same process as in Example 1 was performed, except that no high temperature resistant additive was added.
[0060] Performance Testing:
[0061] 1. Low temperature toughness test:
[0062] Referring to the test requirements of GB / T 1843 "Determination of Izod Impact Strength of Plastics", the nylon materials obtained in Examples 1-4 and Comparative Examples 1-4 were injection molded into notched strips of 80 mm × 10 mm × 4 mm, and the notched impact strengths at 23°C, 0°C, -20°C, and -35°C were tested at an impact energy of 2.75 J, as shown in Table 1.
[0063] Table 1:
[0064]
[0065] 2. High temperature heat deformation temperature test:
[0066] With reference to the test requirements of GB / T 1634.1 "Determination of Deformation Temperature of Plastics under Load Part 1: General Test Method", the nylon material injection molding specimens obtained in Examples 1-4 and Comparative Examples 1-4 were tested under the following conditions: heating rate 120°C / h, load pressure 1.8MPa. The heat deformation temperature (HDT) of the tested materials is shown in Table 2.
[0067] Table 2:
[0068]
[0069]
[0070] 3. High temperature durability evaluation:
[0071] Referring to the requirements of GB / T 1040 "Determination of tensile properties of plastics", the nylon material injection molding specimens obtained in Examples 1-4 and Comparative Examples 1-4 were tested for initial tensile strength, and the test conditions were based on a tensile rate of 50 mm / min. At the same time, the samples were placed in a high temperature environment for periodic heating and cooling cycles, from room temperature to 250°C (heating rate of 5°C / min) for 30 minutes, and naturally cooled to room temperature; after 5 cycles, the material surface was observed for deterioration, and the tensile strength was tested. The properties are shown in Table 3.
[0072] Table 3:
[0073]
[0074] Through glass fiber reinforcement and the treatment of toughening agent and high temperature resistant additive, nylon PA66 shows better low temperature toughness and heat resistance. It not only takes into account the high and low temperature resistance, but also has low high temperature strength loss and is not easy to soften and deform, and can adapt to long-term work in a high temperature environment of 210°C. Obviously, in comparative example 3 without using toughening agent, the toughness of the material in low temperature environment is significantly reduced; in comparative example 4 without using high temperature resistant additive, the strength loss of the material is obvious and the material is deteriorated.
[0075] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A high and low temperature resistant nylon material, wherein the composition of the high and low temperature resistant nylon material comprises, calculated by weight: The composition comprises 45-60 parts of nylon 66, 35-45 parts of reinforcing fiber, 5-10 parts of low-temperature toughening agent, 3-5 parts of high-temperature resistant agent, 0.5-1 part of inorganic lubricant, 0.2-0.5 parts of compatibilizer, 0.2-0.5 parts of antioxidant and 0.2-0.5 parts of copper salt heat stabilizer; wherein the low-temperature toughening agent is an organic-inorganic interpenetrating network structure particle of elastomer, inorganic porous particles and epoxy resin blended and extruded in a mass ratio of 3-5:5-6:1; the high-temperature resistant agent is a composite of titanate, long-chain carboxylic acid calcium salt, silicone and calcium sulfate whisker in a mass ratio of 1:2:2:4; the inorganic porous particles are fumed silica with a particle size less than 2 μm.
2. According to claim 1, a high and low temperature resistant nylon material is characterized by: The reinforcing fibers are selected from alkali-free continuous glass fibers with a fiber diameter of 7 to 13 μm.
3. According to claim 1, a high and low temperature resistant nylon material is characterized by: The inorganic lubricant is selected from one or more of tungsten disulfide, molybdenum disulfide, graphite, barium sulfate, and glass microspheres.
4. The high and low temperature resistant nylon material according to claim 1, characterized in that: The compatibilizer is a silane coupling agent.
5. The high and low temperature resistant nylon material according to claim 1, characterized in that: The antioxidant is selected from one or more of hindered phenol antioxidants, amine antioxidants, phosphorus antioxidants, thioether antioxidants, and metal passivators.
6. The high and low temperature resistant nylon material according to claim 1, characterized in that: The copper salt heat stabilizer is selected from copper phthalocyanine and copper acetate.
7. The method for preparing the high and low temperature resistant nylon material according to any one of claims 1 to 6, wherein the specific preparation method is as follows: S1: The elastomer, inorganic porous particles and epoxy resin are uniformly mixed in a mass ratio of 3-5:5-6:1, and the mixture is extruded through a twin-screw extruder to form particles with an organic-inorganic interpenetrating network structure as a low-temperature toughening agent; S2: Titanate, long carbon chain carboxylic acid calcium salt, silicone, and calcium sulfate whisker are dispersed at a mass ratio of 1:2:2:4 to obtain a high temperature resistant additive; S3: 45-60 parts by weight of nylon 66, 5-10 parts of the low-temperature toughening agent prepared in step S1, 3-5 parts of the high-temperature resistant agent prepared in step S2, 0.5-1 part of an inorganic lubricant, 0.2-0.5 parts of a compatibilizer, 0.2-0.5 parts of an antioxidant, and 0.2-0.5 parts of a copper salt heat stabilizer are uniformly dispersed in a homogenizing pot, and the uniformly dispersed mixture is added to a co-rotating twin-screw extruder for melt extrusion and granulation, and continuous glass fiber is added to the 5th to 6th shearing zone of the co-rotating twin-screw extruder at the same time, and the screw speed and the number of glass fibers added are adjusted to control the fiber weight to 35-45 parts; a high and low temperature resistant nylon material is obtained through screw shearing dispersion, melt extrusion drawing, chain air cooling, pelletizing, screening, drying, and packaging.
8. The method for preparing the high and low temperature resistant nylon material according to claim 7, characterized in that: The elastomer in step S1 is selected from one or more of styrene-maleic anhydride copolymer, maleic anhydride grafted SEBS, maleic anhydride grafted ethylene-octene copolymer, and maleic anhydride grafted ethylene propylene diene monomer rubber.
9. The method for preparing the high and low temperature resistant nylon material according to claim 7, characterized in that: The co-rotating twin-screw extruder in step S3 uses a screw with a length-to-diameter ratio of 40:1; the temperature control of each temperature control zone of the extruder is: zone 1 240-260°C; zone 2 270-275°C; zone 3 280-285°C; zone 4 270-275°C; zone 5 260-265°C; zone 6 240-250°C; zone 7 220-230°C; zone 8 200-210°C; zone 9 200-210°C; zone 10 200-210°C.
Citation Information
Patent Citations
High-toughness high-temperature-resistant nylon composite material and preparation method thereof
CN114316583A
Nylon 66 material and preparation method thereof
CN117165077A
Cold-resistance super tough nylon polyolefin alloy and preparation method thereof
CN101870811A
High-strength and high-toughness modified nylon 66 composite material and preparation method thereof
CN105885406A
Cited By
FDM-based low-temperature nylon material for 3D printing and preparation method thereof
CN122343534A